Chemical and Organoleptic Characteristic Banana Stem Chips Made from Kepok Banana (Musa Acuminata sp.) and Raja Banana (Musa acuminata sp.) - Irawansyah, Dedy; Mushollaeni, Wahyu; Rahmawati, Atina (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2024)
The potential for banana stems to be processed into food products is very large, considering that their utilization is still low so far. One of the processed foods that is popular with the public is chips. Chips have been produced from various types of tubers, but industries that process banana stems into chips are still very rare. If processed properly, banana stem chips can provide quite large profit opportunities. Banana stem chips have a high fiber content which makes them unique as a variety of snacks to meet dietary fiber needs. This study aims to obtain a combination of types of bananas with soaking time using salt, which can produce banana stem chips with the best fiber, water, ash and organoleptic content. The research design used a randomized block design with the first treatment being the type of banana stem (kepok and plantains) and salt concentration (2, 4, and 6%). Variations in the treatment of giving salt baths with levels of 2%, 4% and 6%. The best treatment was P1K3, which was a type of kepok banana soaked in 6% salt with chemical characteristics of 16.98% fiber content, 4.56% moisture content, 0.77% ash content. The organoleptic test showed that the average consumer expressed a real level of liking with a texture value of 4.70; aroma of 4.67; color of 4.63; and taste of 4.64.